Trusted Knowledge for Parents : Tips to Prepare, Position, and Empower Today's Parents. - Culp, Barbara D. (Words of wisdom (Rowman and Littlefield, Inc.), 2016)
Trusted Knowledge for Parents encourages and inspires readers in the most important job of all: that of being a parent. The lessons in this book were forged in the crucible that is parenting. They have been hardened with resolve and experience and, most importantly, with a parent's love. Trusted Knowledge for Parents provides clarity, inspiration and support for raising compassionate, respectful and productive children.